PLaTHEA: a marker‐less people localization and tracking system for home automation. (13th April 2014) - Leotta, Francesco; Mecella, Massimo
Summary Current smart spaces require more and more sophisticated sensors able to acquire the state of the environment in order to provide advanced and customized services. Among the most important environmental variables, locations of users and their identities represent a primary concern for smart home applications. Despite some years of investigation in indoor positioning, the availability of systems designed as components pluggable into complex home automation platforms is limited. We present People Localization and Tracking for HomE Automation (PLaTHEA), a vision‐based indoor localization system specifically tailored for Ambient Assisted Living applications. PLaTHEA features a novel technique to acquire a stereo video stream from a couple of independent (and not synchronized) network‐attached cameras, thus easing its physical deployment. The input stream is processed by integrating well‐known techniques with a novel tracking approach targeted to indoor spaces. The system has a modular architecture that offers clear interfaces exposed as Web services, and it can run on off‐the‐shelf and cheap hardware (both in terms of sensing devices and computing units). We evaluated PLaTHEA in real usage conditions and reported the measured performance in terms of precision and accuracy. Low light, crowded and large monitored environments might slightly decrease the performance of the system; nevertheless, the results here presented show that it is perfectly suitable to be employed in the typical domestic day‐to‐day life settings. Copyright © 2014 John Wiley & Sons, Ltd.